1971
DOI: 10.1115/1.3449786
|View full text |Cite
|
Sign up to set email alerts
|

Mass Flux and Enthalpy Distribution in a Rod Bundle for Single- and Two-Phase Flow Conditions

Abstract: Diabatic multirod subchannel data have been obtained in a 9-rod bundle for operating conditions typical of a boiling water reactor. These data have been used to obtain both the natural flow and enthalpy distribution in a rod bundle and information on the flow diversion enthalpy and the effective flow diversion length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In other words, the vapor or gas moves away from the smaller subchannels toward the larger subchannels. These phenomena were reported by many investigators, e.g., first by Lahey et al 2) and recently by Yadigaroglu et al 3) In general the observed behavior is called "void drift" phenomena. Conventional void drift models are based on the extension of the turbulence diffusion theory described in the textbook of Lahey and Moody.…”
Section: Flow Distribution In a Rod Bundle 1 Inter-subchannel Exmentioning
confidence: 68%
See 1 more Smart Citation
“…In other words, the vapor or gas moves away from the smaller subchannels toward the larger subchannels. These phenomena were reported by many investigators, e.g., first by Lahey et al 2) and recently by Yadigaroglu et al 3) In general the observed behavior is called "void drift" phenomena. Conventional void drift models are based on the extension of the turbulence diffusion theory described in the textbook of Lahey and Moody.…”
Section: Flow Distribution In a Rod Bundle 1 Inter-subchannel Exmentioning
confidence: 68%
“…The hydrodynamic equilibrium flow in a rod bundle or inter-connected subchannel system would be characterized by the following conditions between adjacent subchannels: (1) no pressure differences, (2) no net mass or volume exchanges for each phase, and (3) no net momentum exchanges. It is noted that these conditions are on a time-averaged basis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this code was verified for subcritical pressure and single phase flow conditions. 10) Analysis results and experimental data are compared in Fig. 4.…”
Section: Validation Of Analysis Codementioning
confidence: 99%
“…The conservation equations (2)- (4) The 3×3 rod bundle test conducted by Lahey et al, 13) which was analyzed for the SILFEED code verification, 4) was applied as the first step of the verification of the present subchannel analysis method. They had performed 4 unheated single-phase flow test runs to measure mass flux distribution between subchannels and 13 heated two-phase flow test runs to measure mass flux and quality distributions.…”
Section: Subchannel Analysismentioning
confidence: 99%